Modeling and Optimization of Laser Spectroscopy of the Hyperfine Ground State in Muonic Hydrogen - Ferro, Miguel Carmona Oliveira (2022)
The upcoming HyperMu experiment from the CREMA collaboration aims for a measurement of the ground-state hyperfine splitting (HFS) in muonic hydrogen (μp) by means of pulsed laser spectroscopy as a new route for probing the fine details of proton nuclear structure. In the proposed experimental scheme, the transition from the singlet to the triplet hyperfine state is driven by laser excitation and the excited μp atoms are afterwards quenched back to the singlet state through inelastic collisions with H2 molecules. The kinetic energy increase of the μp atoms after collisional de-excitation greatly increases their probability of detection within the muon’s lifetime, and the population of collisionally quenched μp atoms is therefore used as a model for the probability of a successful detection. In this work a simulation method was developed in order to calculate the combined probability of laser excitation followed by collisional de-excitation of a μp atom under different sets of possible experimental conditions, such as temperature, pressure, laser pulse fluence and time duration and cavity mirror reflectivity and diameter. The implemented simulation allows the calculation of this combined probability from the optical Bloch equations, which were derived for an electric field dependent on the laser and cavity conditions, while also accounting for collisional and Doppler effects. The combined probability was calculated for several sets of different experimental parameters, thus providing a new and alternative method for the optimization of both the temperature and pressure of the H2 gas, where the μp atoms undergo laser excitation, as well as the laser and cavity conditions.